2017
DOI: 10.1104/pp.17.00653
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for Triacylglycerol in Membrane Lipid Breakdown, Fatty Acid β-Oxidation, and Plant Survival under Extended Darkness

Abstract: ORCID IDs: 0000-0002-6821-6583 (J.F.); 0000-0002-0595-081X (L.Y.); 000-0002-0179-9462 (C.X.).Neutral lipid metabolism is a key aspect of intracellular homeostasis and energy balance and plays a vital role in cell survival under adverse conditions, including nutrient deprivation in yeast and mammals, but the role of triacylglycerol (TAG) metabolism in plant stress response remains largely unknown. By thoroughly characterizing mutants defective in SUGAR-DEPENDENT1 (SDP1) triacylglycerol lipase or PEROXISOMAL ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
107
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 78 publications
9
107
2
Order By: Relevance
“…Lipids in membranous organelles are used as alternative substrates for energy production via b-oxidation of fatty acids in mitochondria in mammals (Shatz et al, 2016) and peroxisomes in yeast (Kohlwein, 2010) and plants (Graham, 2008) during times of nutrient scarcity. Emerging evidence suggests that rather than directly being used for b-oxidation, fatty acids released from cellular membranes are first stored in the form of triacylglycerol (TAG) in lipid droplets (LDs), and TAG in LDs is then hydrolyzed by a process named lipolysis to supply the cell with fatty acids for the generation of energy (Cabodevilla et al, 2013;Fan et al, 2014Fan et al, , 2017Rambold et al, 2015). In mammalian cells, autophagic digestion of membranous organelles is the major source of fatty acids for TAG synthesis and LD biogenesis under starvation conditions (Rambold et al, 2015;Nguyen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids in membranous organelles are used as alternative substrates for energy production via b-oxidation of fatty acids in mitochondria in mammals (Shatz et al, 2016) and peroxisomes in yeast (Kohlwein, 2010) and plants (Graham, 2008) during times of nutrient scarcity. Emerging evidence suggests that rather than directly being used for b-oxidation, fatty acids released from cellular membranes are first stored in the form of triacylglycerol (TAG) in lipid droplets (LDs), and TAG in LDs is then hydrolyzed by a process named lipolysis to supply the cell with fatty acids for the generation of energy (Cabodevilla et al, 2013;Fan et al, 2014Fan et al, , 2017Rambold et al, 2015). In mammalian cells, autophagic digestion of membranous organelles is the major source of fatty acids for TAG synthesis and LD biogenesis under starvation conditions (Rambold et al, 2015;Nguyen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of SDP1 blocks TAG hydrolysis in germinating seeds (Eastmond, 2006) and in vegetative tissues such as mature leaves and roots (Kelly et al, 2013;Fan et al, 2014), suggesting that cytosolic lipolysis plays a dominant role in TAG breakdown in both seed and nonseed tissues under normal growth conditions. Under extended darkness, TAG levels in leaves of sugar dependent1 (sdp1) mutants increased rapidly and then declined, suggesting an activation of unknown, alternative pathways for TAG hydrolysis under starvation conditions (Fan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these neutral glycerolipids are more than a carbon and energy reserve in plant storage tissues, being involved in vegetative tissues in cell division and expansion, stomatal opening, and membrane lipid remodelling (Yang & Benning, ). In plants, certain stress conditions have most commonly been linked with TG accumulation, as shown for heat stress, oxidative stress, and prolonged darkness (Higashi, Okazaki, Myouga, Shinozaki, & Saito, ; Fan, Yu, & Xu, ). Physiological functions of stress‐accumulated TG indicate their importance in storage of chemical energy and materials for membrane lipid biosynthesis and remodelling, transient sequestration of free fatty acid (FA), as well as for production of FA‐derived defensive compounds (Shimada, Hayashi, & Hara‐Nishimura, ; Yang & Benning, ), however, a role of TG in salt tolerance has remained understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The former is a more likely scenario given that dic2-1 phenotypes are observed mostly during darkness when fatty acid biosynthesis is ineligible (71), and the transcripts of two peroxisomal citrate synthase isoforms are more abundant at night (72, 73) and during prolonged darkness (74). Lowering fatty acid accumulation by limiting triacylglycerol depletion helps plants survive prolonged darkness by dampening the degree of lipid peroxidation (75). Thus, the increased susceptibility to dark-induced senescence by dic2-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%